STRATEGI KEMENTERIAN AGAMA DALAM MENINGKATKAN MUTU MANAJEMEN MADRASAH ALIYAH DI KABUPATEN SELUMA - Suhirman Suhirman; Idi Syatriawan (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2017)
The purpose of the  research is to describe the  strategy of the  Ministry  of Religious  Affairs in Improving the Quality  of Madrasah Aliyah Management in Seluma District. This type of research includes qualitative research. The subject of this study  was head of Seluma, Head of Madrasah and  principal. Instrument of data  collection using  obser- vation, interview and  documentation, Technique of data  analysis with qualitative data  analysis done interactively and progress continuously until complete, so that data  is saturated. The results of this study indicate that the strategy of the Ministry of Religious Affairs in improving the quality of Madrasah Aliyah management in Seluma Regency by improving the academic and  non  academic quality by meeting the 8 national education standards in accordance with the PP. 32Year 2013 which  includes content standards, process standards, equipment and  infrastructure standards, graduation competency standards, management competency standards, financing competency standards, competency standards of educators and  education personnel as well as assessment competency standards. Constraints experienced by the Ministry  of Religious  Affairs Seluma in improving the  quality of Madrasah Aliyah management such  as teachers and educators who have not met  the academic standards, still low ability to take advantage of IT, and  Infrastructure Inad- equate. The solution to overcome obstacles in improving the  quality of Madrasah Aliyah management by the  Seluma Regency ministry is to motivate teachers to improve their  educational qualifications, to include teachers in workshops and training, to activate KKG activities and to use IT such as internet, communication tools and social media Others. Keywords: Strategy, Ministry  of Religious Affairs, Quality of Madrasah Aliyah Management.